Canonical texts and scholarly practices: a global comparative approach - Grafton, Anthony; Most, Glenn W. (Cambridge University Press, 2016)
How to do things with texts: an introduction Anthony Grafton and Glenn W. Most -- 1. Reliable books: Islamic law, canonization, and manuscripts in the Ottoman Empire (Sixteenth to Eighteenth Centuries) / Guy Burak (New York University) -- 2. Obscurity / Ineke Sluiter (University of Leiden) -- 3. Allegoresis and etymology / Glenn W. Most (Scuola Normale Superiore di Pisa/University of Chicago) -- 4. Classifying the Rigveda on the basis of ritual usage: the deity-of-the-formula system / Paolo Visigalli (University of Munich) -- 5. Maryadam Ullanghya: The boundaries of interpretation in Early Modern India / Christopher Minkowski (University of Oxford) -- 6. Making sense of Suetonius in the Twelfth Century / Robert A. Kaster (Princeton University) -- 7. From Philology to Philosophy: Zhu Xi as a reader-annotator / Lianbin Dai (Harvard University) -- 8. Gods on clay: Ancient Near Eastern scholarly practices and the history of religions / Aaron Tugendhaft (University of Chicago) -- 9. An unknown Medieval Coptic Hebraism? On a momentous junction of Jewish and Coptic biblical studies / Ronny Vollandt (Free University of Berlin) --10. Picturing as practice: placing a square above a square in the Central Middle Ages / Megan McNamee (University of Michigan) -- 11. Inimitable sources: canonical texts and rhetorical theory in the Greek, Latin, Arabic, and Hebrew Traditions / Filippomaria Pontani (University of Venice) -- 12. Excerpts versus fragments: deconstructions and reconstitutions of the Excerpta Constantiniana / András Németh (Vatican Apostolic Library) -- 13. Johann Buxtorf makes a notebook / Anthony Grafton (Princeton University) and Joanna Weinberg (University of Oxford) -- 14. World bibliographies: libraries and the reorganization of knowledge in Late Renaissance Europe / Paola Molino (University of Vienna)